Evaluation of Vertical Handover Performance between WiFi and WiMax Networks using Media Independent Handover - صالحاني محمد; يوسف هبة (Latakia University Journal -Engineering Sciences Series, 2021)
The current researches are moving towards more development in order to provide the growing the needs of users such as support real-time applications, quality of service, particularly; the high data rate transfer and other. That prompts the network service providers to integrate many properties for different networks resource, and support providing the service "anywhere and anytime". Hence, the importance of this research, which aims to study the vertical handover as very important and necessary step to provide the mobility of mobile nodes between the different networks by using Media Independent Handover (MIH) IEEE802.21standard which is developed in January 2009. In this paper, the performance of vertical handover between these two networks is evaluated taking into account many parameters such as packet loss, handover latency, and throughput, using NS2 simulator (Network Simulator version2) which includes a support for MIH technology by the National Institute of Standard and Technology (NIST).